State of New-Hampshire. A proclamation, for a general thanksgiving : ... Thursday, the fourth day of December next ... By order of the Council and Assembly. Exeter, November 17th, 1777 (Printed by Zechariah Fowle, Junr., 1777)
November 17, 1777 Proclamation setting December 4th as a day of thanksgiving in gratitude for war successes and the profusion of nature and God's goodness.